A Question of Segregation: 'GM‐free' Maize Bread in Portugal. (April 2016) - Quedas, Fátima; Ponte, João; Trindade, Carlos; Punt, Maarten; Wesseler, Justus
Summary: We describe the maize supply chain in Portugal for maize bread, a traditional bread type. As this bread is not labelled as 'contains genetically modified organisms' it should not contain more than 0.9 per cent genetically modified ingredients. On the basis of interviews we identify a general lack of documentation of the presence or absence of genetically modified ingredients along the complete supply chain (farmers, traders, mills and bakeries). Part of this deficiency is probably driven by a lack of awareness of the labelling rules at the end of the supply chain. A test of maize bread showed that more than 40 per cent of breads were indeed over the labelling threshold, and should be labelled. This includes GM maize that is not cultivated in the EU and enters the supply chain via international trade. We conclude that the realisation of coexistence and segregation requires involvement of the full supply chain, rather than just segregation at the start, if bread is to be sold with a GMO content below the 0.9 per cent threshold level. Alternatively, retailers can label their bread. This might be a cheaper solution and as a study from Switzerland shows may not result in adverse consumer reaction. Abstract : We describe the maize supply chain in Portugal for maize bread, a traditional bread type. As this bread is not labelled as 'contains genetically modified organisms' it should not contain more than 0.9 per cent genetically modified ingredients. On the basis of interviews we identify a general lack of documentation of the presence or absence of genetically modified ingredients along the complete supply chain (farmers, traders, mills and bakeries). Part of this deficiency is probably driven by a lack of awareness of the labelling rules at the end of the supply chain.